Best practices for disinfection in dental settings: insights from Italian and European regulations - Triggiano, Francesco; Veschetti, Enrico; Veneri, Federica; Montagna, Maria Teresa; De Giglio, Osvalda (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Disinfection practices in dental settings are fundamental to clinical safety, playing a pivotal role in preventing cross-infections and protecting the health of patients and healthcare professionals. This article examines the key components of effective disinfection, based on evidence-based protocols developed by international organizations such as the WHO and the U.S. CDC, alongside European and Italian regulatory standards. Dental instruments require stringent sterilization by autoclave or chemical methods, while high-level disinfection is essential for non-sterilizable items. Clinical surfaces require routine biocidal treatment tailored to microbial hazards and material compatibility. The European Biocidal Products Regulation and the Medical Devices Regulation provide critical oversight, ensuring product safety and effectiveness while preventing resistance. Antiseptics also play a vital role in oral care, with applications ranging from infection prevention to the treatment of periodontal disease, and are governed by strict regulatory frameworks. Disinfection effectiveness is significantly affected by factors such as microbial load, presence of biofilm, pH, temperature and biocide exposure time. Preventing bacterial resistance requires appropriate germicide selection, adherence to manufacturer protocols, robust sterilization and cleaning procedures. In addition, the increased use of disinfection during public health emergencies highlights the need for adaptability to mitigate evolving risks. Regular audits, biological tests, and training for healthcare personnel ensure the consistent application of these rigorous protocols. By integrating international and national standards, dental facilities achieve a uniform approach to hygiene and safety, advancing public trust and compliance. This article highlights the imperative for ongoing research and dissemination of best practices to enhance infection control in dental care environments.